«Պառլամենտարիզմ» հասկացության ըմբռնման շուրջ - Ազատյան, Խոսրովադուխտ (YSU Journal of International Affairs, 2018)
The article is devoted to the study of various approaches to the interpretation of the concept of parliamentarism. In particular, the main points of view of the interpretation  of this phenomenon are considered in political and juridical science, due to the political and juridical essence of this phenomenon. It should be noted, that the approaches of different authors are compared. The complexity and versatility of parliamentarism are underlined. The theoretical and methodological foundations of parliamentarism are revealed. It is shown that parliamentarism includes the political culture of this nation,the degree of legal consciousness, the traditions of political representation.
Keywords: parliamentarism, parliamentary form of government, parliament, public representation, the principle of the separation of powers, political culture